3D biomimetic design of mesenchymal stem cells and endothelial cells promotes the vascularization of tissue engineering scaffold - TAN Jiameng, WU Yu, CHEN Jianwei, ZHU Delong, WANG Kun, ZHU Lei (Xin yixue)
Objective To fabricate 3D biomimetic design of tissue engineering scaffolds（Shell-Core scaffolds）incorporating mesenchymal stem cells（MSCs）and human umbilical vein endothelial cells（HUVECs）by using advanced coaxial 3D bioprinting technology，and to validate the biomimetic vascularization capacity of the scaffolds by experiments. Methods The Shell-Core scaffolds were successfully fabricated via coaxial 3D bioprinting technology. The biomimetic structural features were characterized using optical microscopy and histological staining assay. The in vitro pro-angiogenic capacity was evaluated through inter-group comparative observations and cell scratch assays. Furthermore，qRT-PCR was employed to quantify RNA expression levels of angiogenesis-related markers in cells cultured on the Shell-Core scaffolds. Results Shell-Core scaffolds were successfully fabricated. The scaffolds possessed high structural fidelity，which could be maintained at 7 d after scaffold fabrication. Cell proliferation assay showed that the cell proliferation rate in the scaffolds at 7 d was higher than that in the mixed culture on the 2D plane. Cell scratch assay showed that the shortening scratch distance of HUVECs treated by Shell-Core-CM was significantly greater than those treated by 3D-Mix-CM and blank groups [（431.6±33.6）μm vs.（378.7±22.5）μm vs.（302.3±20.1）μm，both P < 0.01]. At 7 d after in vitro cultured of engineered biomimetic tissues，under fluorescence microscope，HUVECs expressing green fluorescent protein remained in the designed core channel，and self-assembled endothelial buds in all directions. Furthermore，the results of qRT-PCR show that quantified RNA expression levels of angiogenesis-related markers（MMP-9）in cells cultured on the Shell-Core scaffolds was significantly higher（1.55±0.06，P < 0.01）than that in 3D-Mix scaffolds. Conclusions The Shell-Core scaffolds integrating MSCs and HUVECs demonstrates high structural fidelity and pro-angiogenic capacity，offering a novel strategy for addressing tissue defect repair and fabricating vascularized engineered organs. This platform further provides a physiologically relevant tissue model for drug testing and mechanistic investigation of angiogenesis.